2021
DOI: 10.1016/j.ijid.2020.11.152
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus in Nepal: A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(29 reference statements)
3
14
0
Order By: Relevance
“…Also, most of the clinical laboratories in hospitals including national-level ones rely on biochemical tests to identify organisms. By using similar methods, other different studies conducted in Nepal had reported S. aureus as the predominant bacterial pathogen [ 13 , 33 , 35 , 42 ]; moreover, a high prevalence of S. aureus was also found in different parts of the world [ 43 , 44 ]. This variation may be due to the time, type of samples, and the geographical, seasonal/climatic condition [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, most of the clinical laboratories in hospitals including national-level ones rely on biochemical tests to identify organisms. By using similar methods, other different studies conducted in Nepal had reported S. aureus as the predominant bacterial pathogen [ 13 , 33 , 35 , 42 ]; moreover, a high prevalence of S. aureus was also found in different parts of the world [ 43 , 44 ]. This variation may be due to the time, type of samples, and the geographical, seasonal/climatic condition [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 93%
“…The finding of our study was consistent with other previous findings in Nepal [ 30 – 33 ]. However, the prevalence varies in the different parts of Nepal [ 34 , 35 ] and India [ 36 ]. This finding can show the use of beta-lactam antibiotics against Gram-positive organisms in hospital and community settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased incidence of resistance to this antibiotic led to the introduction of methicillin-the first semisynthetic penicillin. Unfortunately, methicillinresistant S. aureus (MRSA) was discovered shortly after, now belonging to multi-drug resistant organisms (MDRO) [38,39]. It is one of the most important serious opportunistic human pathogens involved in nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to methicillin primarily derives from acquisition of the mecA gene, which encodes a modified penicillin-binding protein (PBP2a) with low affinity for beta-lactams [40] The treatment of MRSA infection is greatly challenging since it has developed the resistance to almost all types of antibiotics, especially from the beta-lactam group, including penicillins, cephalosporins, monobactams and carbapenems. MRSA strains have also developed resistance to various other clinically used antibiotics such as fluoroquinolones, macrolides, aminoglycosides, daptomycin, and clindamycin creating a great threat to global healthcare [38,39]. Moreover, recent studies indicates that MRSA is continuously evolving as a superbug.…”
Section: Discussionmentioning
confidence: 99%
“…Households with individuals who work at health-care facilities (OR = 9) and those who regularly visit health-care facilities (OR = 24) have a higher prevalence of MRSA than the normal, healthy population. [ 14 ] Therefore, the S. aureus status among ophthalmic staff noted in the current study can be used to implementing strategies to mitigate the risk of MRSA infections in patients seeking eye care.…”
Section: Discussionmentioning
confidence: 99%